7a²b-(-4a²b+5ab²)-2(2a²b-3ab²)化简后是什
1个回答
7a²b-(-4a²b+5ab²)-2(2a²b-3ab²)
=7a²b+4a²b-5ab²-4a²b+6ab²
=(7a²b+4a²b-4a²b)+(-5ab²+6ab²)
=7a²b+ab²
相关问题
化简:7a²b + (4a²b - 5a²b)- 2(2a²b-3ab²
先化简后再求值;7a²b+(-4ab²)-(7a²b-3ab²)-5ab,其中a=2,b=1
化简 2a-(5ab+b)+(3a-4b-ab)
3a^2-5a∧2+ab-b^2-7ab+7b^2+3a∧2=?化简
化简ab-[3a^2b-(2/3ab+4a^2b)]-(2ab+a^2b)
化简ab-[3a^2b-(2/3ab+4a^2b)]-(2ab+a^2b)
化简5ab-[2(2a²-ab-b²)-3(a²+b²)]-3(ab-2b&su
化简:①-2ab ·(a²-2ab+b);②(a+5b)(5a-b)-(a-2b)².
(1)化简后再求值:5(3a2b-ab2)-4(-ab2+3a2b),其中a=-1,b=-2.
化简ab-2{ab-[3a²b-(4ab²+2/1ab)-3a²b]}-3ab²